2014
DOI: 10.1038/srep03648
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA sequence polymorphisms and the risk of different types of cancer

Abstract: MicroRNAs (miRNAs) participate in diverse biological pathways and may act as oncogenes or tumor suppressors. Single nucleotide polymorphisms (SNPs) in miRNAs (MirSNPs) might promote carcinogenesis by affecting miRNA function and/or maturation; however, the association between MirSNPs reported and cancer risk remain inconsistent. Here, we investigated the association between nine common MirSNPs and cancer risk using data from large scale case-control studies. Eight precursor-miRNA (pre-miRNA) SNPs (rs2043556/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 56 publications
3
57
1
1
Order By: Relevance
“…Mutations of the 3p arm of miR-142 (both-arm type) were recently found in acute myeloid leukemia (AML) 39 , and variation of the 3p arm of immune-related miR-146a has been reported to be associated with the risks of acquiring various types of cancer 40,41 (schematic of mutations in Fig. 8a).…”
Section: Asymmetry Alteration By Cancer-related Mirna Variationsmentioning
confidence: 99%
“…Mutations of the 3p arm of miR-142 (both-arm type) were recently found in acute myeloid leukemia (AML) 39 , and variation of the 3p arm of immune-related miR-146a has been reported to be associated with the risks of acquiring various types of cancer 40,41 (schematic of mutations in Fig. 8a).…”
Section: Asymmetry Alteration By Cancer-related Mirna Variationsmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) are non-coding RNAs with complex biological functions that regulate the expression of numerous proteins through direct binding to the 3'-untranslated region of target genes (15,16). It has been well-documented that miRNAs are involved in a wide range of ovarian cancer tumorigenic processes, including malignant transformation, differentiation, proliferation and apoptosis (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…5) [24][25][26][27][28]. For example, it has been proved by previous study that a higher level of miR-166 expression was observed within normal prostate tissues compared with cancer patients, which inhibited the growth of prostate tumor by regulating the expression of genes associated with cellular proliferation and cell cycle control, such as CDK1 and CDK2 [29].…”
Section: Cancer Cells Intrude Into the Blood And Lymphatic Vesselsmentioning
confidence: 90%